2005
DOI: 10.1186/1471-2350-6-21
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric study of 132 patients with mental retardation reveals 9 chromosomal anomalies and contributes to the delineation of submicroscopic deletions of 1pter, 2qter, 4pter, 5qter and 9qter

Abstract: Background: Cryptic chromosome imbalances are increasingly acknowledged as a cause for mental retardation and learning disability. New phenotypes associated with specific rearrangements are also being recognized. Techniques for screening for subtelomeric rearrangements are commercially available, allowing the implementation in a diagnostic service laboratory. We report the diagnostic yield in a series of 132 subjects with mental retardation, and the associated clinical phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Nearly 100 individuals carrying isolated, primarily terminal deletions with breakpoint at or within chromosome 2 region q37 have been reported previously [Gorski et al, 1989;Lamb et al, 1990;Coldwell et al, 1992;Lin et al, 1992;Oley et al, 1992;Haag et al, 1993;Waters et al, 1993;Fisher et al, 1994;Stratton et al, 1994;Wang et al, 1994;Conrad et al, 1995;Phelan et al, 1995;Wilson et al, 1995;Rauch et al, 1996;Friedman et al, 1997;Power et al, 1997;Wenger et al, 1997;Viot-Szoboszlai et al, 1998;Ghaziuddin and Burmeister, 1999;Reddy et al, 1999;Lehman et al, 2001;Smith et al, 2001;Anderlid et al, 2002;Wolff et al, 2002;van Karnebeek et al, 2002;Giardino et al, 2003;Aldred et al, 2004;Casas et al, 2004;Chassaing et al, 2004;Lukusa et al, 2004;Polityko et al, 2004;Shrimpton et al, 2004;Adeyinka et al, 2005;Sogaard et al, 2005;Chaabouni et al, 2006;Lacbawan et al, 2006;Masumoto et al, 2006;Ravnan et al, 2006], though some of the reports have not included detailed clinical characterization. In addition Nearly 100 individuals carrying isolat...…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nearly 100 individuals carrying isolated, primarily terminal deletions with breakpoint at or within chromosome 2 region q37 have been reported previously [Gorski et al, 1989;Lamb et al, 1990;Coldwell et al, 1992;Lin et al, 1992;Oley et al, 1992;Haag et al, 1993;Waters et al, 1993;Fisher et al, 1994;Stratton et al, 1994;Wang et al, 1994;Conrad et al, 1995;Phelan et al, 1995;Wilson et al, 1995;Rauch et al, 1996;Friedman et al, 1997;Power et al, 1997;Wenger et al, 1997;Viot-Szoboszlai et al, 1998;Ghaziuddin and Burmeister, 1999;Reddy et al, 1999;Lehman et al, 2001;Smith et al, 2001;Anderlid et al, 2002;Wolff et al, 2002;van Karnebeek et al, 2002;Giardino et al, 2003;Aldred et al, 2004;Casas et al, 2004;Chassaing et al, 2004;Lukusa et al, 2004;Polityko et al, 2004;Shrimpton et al, 2004;Adeyinka et al, 2005;Sogaard et al, 2005;Chaabouni et al, 2006;Lacbawan et al, 2006;Masumoto et al, 2006;Ravnan et al, 2006], though some of the reports have not included detailed clinical characterization. In addition Nearly 100 individuals carrying isolat...…”
Section: Introductionmentioning
confidence: 88%
“…Clinically significant microdeletions usually occur as de novo events, but exceptions have been noted. Sogaard et al [2005] reported a phenotypically normal mother with the 2q37.3 deletion polymorphism whose child had mental retardation and physical anomalies associated with a larger 6.8 Mb 2q37 microdeletion. van Karnebeek et al [2002] …”
Section: Molecular Aspects Of Deletion 2q37mentioning
confidence: 98%
“…A polymorphism at the 2q telomere was first identified by Macina et al [1994] and using multiple subtelomeric probes in a study of 150 patients, indicated that 6% of these patients had a 2qtel deletion and they concluded that the deletion of the locus D2S2986 in the 2qtel region was a common variant. Sogaard et al [2005] reported a phenotypically normal mother with a 2q37.3 deletion polymorphism whose child had clinical manifestations associated with a larger microdeletion (6.8 Mb). Similarly, Van Karnebeek et al [2002] described a microdeletion distal to 2q37.3 in a phenotypically normal father whose daughter showed clinical manifestations of a 2q37.3 terminal deletion.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 98%
“…A precise mapping of the deletions, however, was carried out in only a few studies (27/115 patients). [1][2][3][4][5][6][7][8][9][10]13,14,24,25,30,32 The patients with purely distal deletions (seven females, three males) included in the DECIPHER database (http://decipher.sanger.ac.uk/) had various deletion sizes ranging from 3 to 9.9 Mb. Unfortunately, clinical features were only mentioned for 2 of the 10 patients.…”
Section: Mappingmentioning
confidence: 99%